The thickness and volume of LLETZ specimens can predict the relative risk of pregnancy-related morbidity - Khalid, S; Dimitriou, E; Conroy, R; Paraskevaidis, E; Kyrgiou, M; Harrity, C; Arbyn, M; Prendiville, W (BJOG : an international journal of obstetrics and gynaecology, 2012)
Please cite this paper as: Khalid S, Dimitriou E, Conroy R, Paraskevaidis E, Kyrgiou M, Harrity C, Arbyn M, Prendiville W. The thickness and volume of LLETZ specimens can predict the relative risk of pregnancy‐related morbidity. BJOG 2012;119:685–691. Objective  The aim of this study was to determine if the individual physical characteristics of the extirpated transformation zone after large loop excision of the transformation zone (LLETZ) might predict the relative risk of adverse obstetric outcome, specifically preterm labour (PTL). Design  A retrospective observational study. Setting  University teaching hospital in Dublin (Coombe Women & Infants University Hospital, CWIUH). Population  Women who had LLETZ treatment for cervical intraepithelial neoplasia (CIN) in the colposcopy service between 1999 and 2002, and who subsequently had a pregnancy at the CWIUH. Methods  Case records and histology reports for eligible women were examined. Age, parity, smoking history, pregnancy complications and CIN grade were recorded. Exclusion criteria were age >42 years, previous treatment for CIN, previous premature labour or twin pregnancies. The Student’s t‐test, Mann–Whitney U‐test, analysis of variants (ANOVA) and logistic regression were employed to analyse the data. Main outcome measures  Gestational age at birth, PTL (i.e. <37 weeks of gestation) and miscarriage rate (<24 weeks of gestation). Results  Out of 1808 women who underwent LLETZ treatment, a total of 353 women were identified who subsequently had a pregnancy at the CWIUH, with 321 being eligible for inclusion in the study. Of these, 76.3% delivered at term, 9.1% delivered at <37 weeks of gestation and 14.6% miscarried at <24 weeks of gestation. There was a three‐fold increase in the risk of PTL if the excision volume exceeded 6 cm3 (RR = 3.00; 95% CI 1.45–5.92), or when the thickness of the excised tissue was greater than 12 mm (RR = 2.98; 95% CI 1.27–7.01). The time interval between LLETZ and pregnancy did not appear to have an effect on PTL rates. We found no association between the grade of CIN and the risk of PTL. Conclusions  This study reveals that the thickness and the total volume of the excised transformation zone are associated with an increased risk of PTL. Excisions thicker than 1.2 cm and larger than 6 cm3 carry a three times greater risk for PTL.